Traffic-related air pollution and endurance exercise: Characterizing non-targeted serum metabolomics profiling. (15th December 2021) - Cruz, Ramon; Pasqua, Leonardo; Silveira, André; Damasceno, Mayara; Matsuda, Monique; Martins, Marco; Marquezini, Mônica V.; Lima-Silva, Adriano Eduardo; Saldiva, Paulo; Bertuzzi, Romulo
Abstract: Although the exposure to traffic-related air pollution (TRAP) has emerged as one of main problem worldwide to inhabitants' health in urban centers, its impact on metabolic responses during exercise is poorly understood. The aim of study was to characterize the profile of non-target serum metabolomics during prolonged exercise performed under TRAP conditions. Ten healthy men completed two 90 min constant-load cycling trials under conditions of either TRAP or filtered air. Experimental trials were performed in a chamber located on an avenue with a high volume of vehicle traffic. Blood samples were taken at 30 min, 60 min, and 90 min of exercise. Based on Nuclear Magnetic Resonance metabolomics, the non-target analysis was used to assess the metabolic profile. Twelve, 16 and 18 metabolites were identified as discriminants. These were: at 30 min of exercise, the coefficient of determination (R 2 ) 0.98, the predictive relevance, (Q 2 ) 0.12, and the area under the curve (AUC) 0.91. After 60 min of exercise: (R 2 : 0.99, Q 2 : 0.09, AUC: 0.94); and at 90 min of exercise (R 2 : 0.91, Q 2 : <0.01, AUC: 0.89), respectively. The discriminant metabolites were then considered for the target analysis, which demonstrated that the metabolic pathways of glycine and serine metabolism ( p  = 0.03) had been altered under TRAP conditions at 30 min of exercise; arginine and proline metabolism ( p  = 0.04) at 60 min of exercise; and glycolysis ( p  = 0.05) at 90 min of exercise. The present results suggest that exposure to TRAP during prolonged exercise leads to a significant change in metabolomics, characterized by a transitional pattern and lastly, impairs the glucose metabolism. Highlights: Exercising under TRAP exposure seems to induce an effect on transitional metabolic. Metabolic pathway alteration linked to insulin resistance was identified at 30-min of exercise. Metabolic pathway alteration linked to inflammation was identified at 60-min of exercise. The transitional pattern has suggested that the glucose metabolism was impaired after 90-min of exercise.